Unity‑Based History Hunt: Development and Quasi‑Experimental Effects on Elementary Students’ Knowledge and Interest - Rani Yuniar; Rizki Hikmawan (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study employed a Research and Development (R&D) approach using the ADDIE model to develop the History Hunt game and then examined its effectiveness using a quasi-experimental pretest-posttest control-group design. Participants were 87 fourth- and fifth-grade elementary students, assigned to an experimental group (n=44) and a control group (n=43). Data were collected with a 10-item historical knowledge test, a 15-item learning-interest questionnaire, a 10-item usability scale, interviews, and classroom observations. The product achieved 82.04% usability, indicating it is suitable for classroom use. Learning outcomes favored the experimental group: N-Gain=0.725 versus 0.566 in the control (t(85)=2.39, p=0.019, Cohen's d=0.513). Learning interest also rose markedly in the experimental group (M=60.36) compared with the control (M=46.23; p<0.001, Cohen's d=2.81). These findings indicate that a Unity-based, location-enabled, game-based learning tool can meaningfully strengthen both historical knowledge and interest in elementary history. Pedagogically, combining game-based learning, location-based tasks, and joyful learning principles offers a feasible, engaging approach for teachers and a replicable development workflow for designers using the ADDIE model.